Genetic Evidence of Expansion by Passive Transport of Aedes (Stegomyia) aegypti in Eastern Argentina - Díaz Nieto, Leonardo M. (2016)
Aedes (Stegomyia) aegypti (Linnaeus) (Diptera: Culicidae) is the principal vector of the yellow fever virus, the five dengue virus serotypes (DENV-1 to DENV-5), chikungunya virus, Zika virus, and several types of encephalitis [1–3]. The behavior of this species is synanthropic and anthropophilic, being the culicid most closely associated with human populations [4]. The incidence of dengue has increased 30-fold over the last 50 years; according to the World Health Organization, up to 50–100 million infections occur each year in over 100 endemic countries, and at least one half of the world’s population has risk of being infected with dengue virus [5]. Chikungunya virus has been responsible for over 2 million human infections during the past decade and is currently moving to subtropical latitudes as well as to the western hemisphere. Up until April 2015, there have been 1,379,788 suspected cases of this disease in the Caribbean islands, Latin America, and the United States. This expansion into novel habitats brings unique risks associated with further spread of the virus and the disease it causes [6]. On the other hand, there are about 200,000 cases of yellow fever each year worldwide responsible for about 30,000 deaths, most of them from Africa. Zika virus is an emerging mosquito-borne virus, with outbreaks in Africa, Asia, and the Pacific between 2007 and 2014. Since 2015, there has been an increase in reports of ZIKV infection in the Americas, with Brazil being the most affected country, with 534 confirmed cases and 72,062 suspected cases between 2015 and 2016 [7]. All these viruses and the mosquito vector A. aegypti present in the Americas represent a serious risk. So far, in 2016, 39,926 dengue cases produced by DENV-1 and DENV-4 serotypes and 319 autochthonous cases of chikungunya fever have been reported in Argentina. According to the last census, Argentina has approximately 40 million people (National Institute of Statistics and Censuses of Argentina [INDEC], Census 2010), and over 38 million live in areas suitable for the transmission of dengue and chikungunya viruses [8]. Moreover, although there were 22 imported cases of Zika and 24 autochthonous cases confirmed in Argentina, there is a high incidence of cases in Brazil, and besides that, there is an internal circulation of the virus in the neighboring countries Brazil, Paraguay, and Bolivia [7,8], in addition to the constant expansion of the mosquito vector.